ANALISIS TINDAK TUTUR DALAM BUKU BACAAN â€œLEGENDA CERITA RAKYAT NUSANTARAâ€ - Pratiwi, Asti Nur; Nugraheni, Aninditya Sri (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2020)
Abstract                This mini research aims to: (1) explain and describe speech acts such as what is used in writing the book